The association of smoking and alcohol in colorectal cancer in black patients – Case-control study - Mpho K. Kgomo; Ratidzo L. Zingoni; Piet J. Becker (Journal of Public Health in Africa)
Background: Studies have focused on smoking and alcohol as risk factors for colorectal cancer (CRC). Caucasians and other populations have been studied worldwide, and both smoking and alcohol have been validated as causes of CRC. However, there are limited data on the black population; studies that have been performed in Africa have not specifically focused on these two risk factors but rather in combination with other risks.